(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In principle, informed consent is a condition of practising medical acts. However, it is arguable if this concept should be applied to persons in an emergency state and persons with infectious diseases under Portuguese law. This article gives a positive answer. In particular cases, the Portuguese legal framework allows situations where consent is not needed when applying compulsive medical acts to specific groups of persons. Nonetheless, this article defends the necessity of the duty to inform before or after compulsive medical actions. This point of view is based on the reasoning that such a duty is not intended to obtain consent and respect patients’ autonomy but to respect other fundamental rights regulated in the Portuguese Constitution, such as access to personal data or the right to information.